PELATIHAN CARA MENGUKUR KINERJA TENAGA PENJUALAN - Rasyid, Ardiansyah; Puswita Anhar, Dela Asokawati; Puspita, Elizabeth Christinio (Transpublika Publisher, 2023)
The strategic role of salespeople in achieving success in selling company products cannot be underestimated. Improving the performance of salespeople is crucial, with the hope that it can make a significant contribution to increasing sales volume and achieving predetermined goals. The focus of this community service activity is to provide assistance to business owners so that they have a deep understanding of sales force performance measurement methods, enabling business owners to optimize their sales. The partner selected for this community service project is a honey business with the brand